Assessment of the Parameters of the State of Natural Objects in the Territory of Agdam Region Based on Multi-Temporal Space Images - Asgerov, K.A.; Fatiyeva, E.F. (Herald of Azerbaijan Engineering Academy, 2022)
With the use of satellite data from Landsat and Azersky, the state of the natural-territorial objects in the territories liberated from the Armenian occupation was carried out. The calculation of the values of vegetation indices made it possible to determine the degree of destruction of green spaces, including forests.